Non-compact carbon-ceramic friction material as well as preparation method and application thereof
By adopting a non-tight structure design in carbon ceramic friction materials and using silicon permeation treatment of C/C-Si blank and silicon powder, the existing carbon ceramic friction materials are solved instability in performance under high temperature and extreme operating conditions, and the effect of lightweight, high strength, high temperature resistance and stable friction performance is achieved.
Patent Information
- Application Number
- CN202411846866.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The existing carbon ceramic friction materials show unstable friction performance, insufficient wear resistance and large weight under high temperature and extreme operating conditions, making it difficult to meet the needs of lightweight, high strength, high temperature resistance, small wear and stable friction performance.
Non-density carbon ceramic friction material is used, which is obtained by silicon-permeable silicon-permeable treatment of C/C-Si blank. The preparation raw materials of the blank include chopped carbon fiber, graphite powder, ferrosilicon mixture, silicon carbide powder, boron nitride powder and phenolic resin powder. Through specific powder particle size and formula design, the porosity and structure of the material are controlled to achieve the preparation of non-density compounds.
The lightweight (density 1.8-2.2g/cm3), high temperature stability (high temperature resistance limit temperature 1350℃), small wear and stable friction coefficient are achieved, significantly improving the performance of the material under extreme operating conditions.
Smart Images

Figure CN119663142A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of carbon-ceramic composite materials, and in particular to a non-dense carbon-ceramic friction material and a preparation method and application thereof. Background Art
[0002] Various types of transportation vehicles, represented by automobiles and high-speed trains, have increasingly higher requirements for their braking systems to achieve reliable braking at high speeds, heavy loads, and complex environments. This puts forward more stringent requirements on the temperature resistance limit, friction and wear performance, and stability of brake friction materials. At the same time, it also requires the material to be light in weight to achieve lightweighting.
[0003] Existing friction plate preparation materials include resin-based friction materials, powder metallurgy friction materials, and dense carbon ceramic materials. However, these preparation materials each have different defects when matched with brake discs, resulting in limitations in the application of the prepared friction plates.
[0004] In the existing technology, most carbon-ceramic brake discs are matched with resin-based friction plates. However, resin-based friction materials will decompose at temperatures above 400°C. At the same time, the surface of the friction plates made may be gray, dull, loose, and have large waste edges. Hot-pressed semi-finished products may have cracks, bubbles, and stratification, causing the performance of the friction plates to deteriorate.
[0005] Powder metallurgy friction plates are made by mixing, pressing and sintering metal-based powdered materials at high temperatures. So far, they have only been tested and studied in high-speed train applications. When matched with carbon-ceramic brake discs, they are heavy, which is not conducive to weight reduction, and there are few actual application scenarios. The melting point of the Cu matrix is only 1083°C, which limits the long-term service limit temperature of the friction plate to below 800°C, and cannot adapt to extreme working conditions.
[0006] The porosity of dense carbon-ceramic friction materials is below 8 vol.%, and they can currently serve for a long time at temperatures above 1000°C. However, as friction plate materials, they have technical problems such as unstable friction performance and insufficient wear resistance. For example, in the Journal of the European Ceramic Society, the author Nico Langhof et al. concluded in Fig. 4 of the document Full-ceramic brake systems for high performance friction applications that the friction coefficient stability of carbon-ceramic friction plates C / SiC SF and C / SiC SF 11Coke is not as good as that of resin-based friction plates Low Met. In Fig. 10, it can be concluded that the wear amount of dense carbon-ceramic friction plates, C / SiC SF made of the same material as carbon-ceramic brake discs, and coke-modified C / SiC SF11Coke are all greater than that of resin-based friction plates (Low Met). For example, in the journal Tribol Lett, the authors Gen Li et al. concluded in Fig. 2 of the literature Comparison of Friction and Wear Behavior Between C / C, C / C-SiC and Metallic Composite Materials that the friction coefficient stability of carbon-ceramic friction plates (C / C-SiC) is not as good as that of metal-based friction plates (metallic), and in Fig. 3 they concluded that the wear rate of carbon-ceramic friction plates (C / C-SiC) is greater than that of metal-based friction plates (metallic). Even though CN117024152A discloses a low-cost carbon ceramic brake material and its preparation method, the existing carbon ceramic material is improved, carbon fibers are sheared to obtain chopped fibers, chopped fibers, calcined petroleum coke, phenolic resin, hexamethylenetetramine, nano zirconium silicate powder, and vermiculite powder are mixed to obtain a mixture, the mixture is pressed to form a blank, the blank is carbonized to obtain a carbonized blank, the carbonized blank is reacted and siliconized to obtain a carbon ceramic blank, the carbon ceramic blank is further subjected to silicon impurity removal treatment, and finally polishing is performed to obtain a carbon ceramic brake material. This technical solution contains a silicon impurity removal step, and the silicon liquid will react and deposit on the surface during the precipitation process to form a uniform and dense silicon carbide layer. However, if it is prepared into a friction plate and rubbed against a brake disc, the surface is a uniform and dense silicon carbide layer, and the technical problem of poor adjustment of traditional dense friction plates and brake discs cannot be overcome during the friction process; and petroleum coke belongs to amorphous carbon, and due to its complex composition, its properties are affected by factors such as ash, sulfur, and volatile matter, and there are a large number of defects in the microstructure. These defects may be difficult to completely eliminate during the calcination process, thus affecting the performance of the final product. At present, there are no reports on non-dense carbon-ceramic composite materials.
[0007] Based on the above situation, there are urgent technical problems to be solved in the prior art in which the materials used to prepare friction plates cannot simultaneously meet the requirements of light weight, high strength, high temperature resistance, low wear, stable friction performance, and adaptability to extreme working conditions. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a non-dense carbon ceramic friction material, wherein the non-dense carbon ceramic friction material is obtained by subjecting a C / C-Si blank to siliconization treatment with silicon powder, and the raw materials for preparing the C / C-Si blank include chopped carbon fiber, graphite powder, ferrosilicon mixture, silicon carbide powder (SiC powder), boron nitride powder (BN powder), and phenolic resin powder; The non-dense carbon ceramic friction material has a porosity of 15-25 vol.%, a high temperature resistance limit temperature of 1350° C., and a compressive strength of 80.5±2.4 MPa.
[0009] Furthermore, the density of the non-dense carbon ceramic friction material is 1.8-2.2 g / cm 3 .
[0010] Furthermore, in parts by weight, the components and proportions of the raw materials for preparing the C / C-Si blank are as follows: Chopped carbon fiber: 15-35%; Graphite powder: 5-10%; Ferrosilicon mixture: 30-50%; Silicon carbide powder (SiC powder): 5-10%; Boron nitride powder (BN powder): 3-8%; Phenolic resin powder: 15-30%.
[0011] Furthermore, the volume content of silicon carbide in the overall non-dense carbon-ceramic friction material is 15-30%.
[0012] Furthermore, the pore diameter of the non-dense carbon ceramic friction material is 10-200 μm.
[0013] Furthermore, the mass ratio of the C / C-Si blank to the silicon powder is 1:2.
[0014] Furthermore, the length of the chopped carbon fiber is 3-6 mm, and the chopped carbon fiber is composed of one or more chopped carbon fibers of different lengths, and the carbon content of the chopped carbon fiber is ≥95wt.%.
[0015] Furthermore, the chopped carbon fiber is a product obtained by chopping carbon fiber filaments by a fiber cutting machine.
[0016] Furthermore, the carbon fiber filaments also include carbon fiber prepregs obtained by modifying carbon fiber filaments, such as carbon fiber prepregs obtained by pre-impregnating carbon fiber filaments with resin.
[0017] Furthermore, the graphite powder has a particle size of 150 mesh and a carbon content of ≥96wt.%.
[0018] Furthermore, the ferrosilicon mixture is one or more Fe-Si alloy powders of the standard grade ferrosilicon specified in GB / T 2272-2020, or a mixture thereof with Si powder in any proportion.
[0019] Furthermore, the Fe-Si alloy powder is one or more of FeSi40, FeSi65, FeSi75, and FeSi90.
[0020] Furthermore, the particle size of the ferrosilicon mixture is 150-350 meshes.
[0021] Furthermore, the particle size of the silicon carbide powder (SiC powder) is 200-300 mesh.
[0022] Furthermore, the particle size of the boron nitride powder (BN powder) is 800-1000 mesh.
[0023] Furthermore, the phenolic resin powder is a thermosetting phenolic resin powder with a particle size of 400-600 meshes.
[0024] Furthermore, the particle size of the silicon powder is 100-150 mesh, and the silicon purity is ≥99wt.%.
[0025] The present invention provides a method for preparing a non-dense carbon ceramic friction material, comprising the following steps: Step 1, weighing short carbon fiber, graphite powder, ferrosilicon alloy powder, silicon carbide powder (SiC powder), boron nitride powder (BN powder), and phenolic resin powder, and mixing them to obtain a mixed powder; Step 2, heating, pressing and curing the mixed powder in step 1 to obtain a green blank; Step 3, carbonizing the green body obtained in step 2 to obtain a C / C-Si body; Step 4: using silicon powder to perform melt siliconization treatment on the C / C-Si blank obtained in step 3 to obtain the non-dense carbon ceramic friction material.
[0026] Furthermore, in step 1, a double motion mixer is used to mix the prepared raw materials at room temperature for 20-60 minutes; The purpose of using a double-motion mixer is: on the one hand, it is to mix more evenly than a V-type mixer (which mixes materials only by rotating the barrel), and on the other hand, it is to prevent the chopped carbon fiber from being coated with powder and forming balls during the mixing process.
[0027] Furthermore, the specific steps in step 2 are: filling the mixed powder into a metal mold, placing the metal mold between the upper and lower pressing plates of a flat vulcanizer, heating the upper and lower pressing plates of the flat vulcanizer to 80°C, keeping warm for 5-30 minutes, and preheating and keeping warm the metal mold and the mixed powder; after the insulation is completed, heating the upper and lower pressing plates of the flat vulcanizer to 180°C, setting a pressure of 20MPa to pressurize the metal mold to liquefy the phenolic resin powder, and bonding the remaining powder, and then releasing the pressure to normal pressure after keeping warm and pressurizing for 20-30 minutes, and stopping heating the upper and lower pressing plates at the same time, waiting for the mold to cool naturally to room temperature, and the phenolic resin to solidify, so that the sample is then demolded and taken out to obtain a blank.
[0028] Furthermore, the metal mold can be a mold of any shape according to actual needs, such as a cylindrical mold or a friction plate-shaped mold.
[0029] Furthermore, the specific steps of carbonization in step 3 are: after evacuating to a vacuum degree of 10Pa, nitrogen is introduced into the furnace to expel the air, and then the temperature is raised to 900°C at a rate of 1-5°C / min, and the temperature is kept for 0.5-3h. Nitrogen is continuously introduced during the heating and insulation process to maintain the pressure in the furnace at 0-0.04 MPa; after the insulation is completed, heating is stopped, and nitrogen is stopped after the temperature in the furnace drops to 300°C, and the temperature in the furnace is continued to cool to room temperature. The sample is taken out to obtain a C / C-Si blank.
[0030] Furthermore, in step 3, under the conditions of air isolation and high temperature, the phenolic resin decomposes, and the hydrogen and oxygen elements therein are removed to form volatile products, such as hydrogen, oxide, water, etc., which are discharged from the system sample, and the remaining carbon element is retained in the C / C-Si body.
[0031] Furthermore, the specific steps of siliconizing treatment in step 4 are: preparing silicon powder, spreading the silicon powder on the bottom of the graphite crucible, and placing the C / C-Si blank obtained in step 3 above the silicon powder; placing the graphite crucible in a high-temperature furnace, evacuating the furnace, and heating the furnace temperature to 1500-1700°C at a rate of 5°C / min, and keeping it warm for 1-2 hours, during which the silicon powder melts into liquid silicon. In the vacuum state, the liquid silicon enters the C / C-Si blank through the pores or contacts the surface of the C / C-Si blank, and a part of it reacts with the C in the C / C-Si blank to generate SiC, while the incompletely reacted liquid silicon is also retained in the pores or on the surface; after the insulation is completed, the heating is stopped, and the temperature in the furnace is waited to drop to room temperature, and then the blank material after siliconizing treatment is taken out to obtain a non-dense carbon ceramic friction material.
[0032] Furthermore, the mass of the silicon powder is twice the mass of the C / C-Si blank in step 3.
[0033] The present invention also provides a friction plate, which is made of the above-mentioned non-dense carbon ceramic friction material; In the AK-master program test, the wear amount of the friction plate is 52.8-95.0 μm; the friction coefficient is 0.6-0.7.
[0034] Furthermore, when preparing the non-dense carbon ceramic friction material, the shape of the mold used matches the shape of the friction plate.
[0035] The present invention also provides a braking device, which includes the above-mentioned friction plate.
[0036] Furthermore, the braking device also includes a brake disc.
[0037] Furthermore, the brake disc is a carbon-ceramic brake disc.
[0038] Furthermore, the braking device also includes a caliper, a brake pipeline, and a connecting piece.
[0039] The present invention also provides a car, comprising the above-mentioned braking device.
[0040] The present invention also provides an aircraft, comprising the braking device.
[0041] The present invention also provides a high-speed railway, which comprises the above-mentioned braking device.
[0042] The beneficial effects of the present invention are: 1. The non-dense carbon ceramic friction material prepared by the present invention is obtained by subjecting a C / C-Si blank to siliconization treatment with silicon powder, wherein the raw materials for preparing the C / C-Si blank include chopped carbon fiber, graphite powder, ferrosilicon mixture, silicon carbide powder (SiC powder), boron nitride powder (BN powder), and phenolic resin powder; Compared with the friction materials in the prior art (such as resin-based friction materials, metal-based powder metallurgy materials, or dense carbon ceramic materials), it has the following advantages: Non-dense: The non-dense carbon-ceramic friction material prepared by the present invention has a porosity of 15-25 vol.%. The existing carbon-ceramic material adopts the method of weaving carbon fibers into a preform to form a carbon-carbon composite material with micron-level pores, and then performs siliconization densification by saturated melt infiltration. However, the amount of pores filled in the carbon-carbon composite material during the melt infiltration process of this preparation process is relatively uncontrollable, and densification can only be achieved by saturated infiltration. The carbon-ceramic material finally obtained is nearly dense, and the porosity is below 8 vol.%; the present invention utilizes a specific powder particle size to first obtain a C / C-Si blank with large-sized pores, and at the same time combines a specific formula and ratio to produce an interactive interface, so that the pores cannot be completely filled during the siliconization process, that is, the non-dense carbon-ceramic friction material with a specific porosity of the present invention is obtained; Lightweight: The average density of non-dense carbon ceramic friction materials is 1.8-2.2g / cm 3 , which is less than the density of resin-based friction materials and only 1 / 3-1 / 2 of the density of metal-based powder metallurgy materials; High temperature resistance: The temperature resistance limit can reach 1350℃, which is much higher than the temperature resistance limit of 400℃ for resin-based friction materials and 800℃ for metal-based powder metallurgy materials; 2. The non-dense carbon ceramic friction material of the present invention is prepared into a friction plate. When it is matched with an existing ordinary dense carbon ceramic brake disc, it has the following advantages compared with the existing friction plate: Small wear amount: The friction plate made of the non-dense carbon ceramic material of the present invention is tested by the AK-master program on an inertia reduction test bench. After the test, the wear amount of the friction plate is 52.8-95.0 μm. Under the same conditions, the wear amounts of the friction plates made of metal-based powder metallurgy materials and resin-based friction materials are 185.7 μm and 534.4 μm, respectively. High porosity: The porosity between 15-25 vol.% can ensure that the prepared friction plate has uniform pores on the surface and inside. Compared with the carbon ceramic material with a uniform and dense silicon carbide layer on the surface disclosed in the prior art such as CN117024152A, the friction plate prepared by the present invention has pores uniformly distributed on the surface and inside of the material, which can capture hard wear debris particles during braking, effectively alleviate the typical abrasive wear phenomenon of the friction plate during braking friction, and significantly reduce the amount of material wear; Stable friction coefficient: The AK-master test program was used to conduct the braking test. In the thermal decay stage, the friction plate made of non-dense carbon ceramic material matched with the ordinary dense carbon ceramic brake disc did not experience thermal decay of the friction coefficient, and the friction coefficient was stable between 0.6-0.7; the friction coefficient of the metal-based powder metallurgy friction plate ranged from 0.5-0.7; the friction coefficient of the resin-based friction plate ranged from 0.3-0.5; the friction coefficient of the high-density carbon ceramic friction plate ranged from 0.6-0.9. The range of the friction coefficient is larger than that of the friction plate prepared by the present invention, and is not stable enough; Short process cycle: Traditionally, chemical vapor deposition densification is used to obtain high-density carbon ceramic materials, and the total process cycle is as long as three months. The present invention adopts a short-cut carbon fiber mixed material molding and then carbonization process to obtain a C / C-Si blank, and finally melt-siliconizes to obtain a non-dense carbon ceramic friction material. The total process time is shortened to within 7 days, which significantly shortens the process time and can improve production efficiency. 3. The graphite powder introduced in the preparation of the raw materials of the present invention exists in the non-dense carbon ceramic friction material. When the friction plate is used as the preparation material, the graphite powder in the material plays a lubricating effect when rubbing against the brake disc during the braking process. Compared with the use of petroleum coke in the prior art, it is more conducive to stabilizing the friction coefficient and reducing the amount of wear; 4. Since the non-dense carbon ceramic friction material prepared by the present invention can withstand a temperature limit of 1350°C, it can be prepared into a friction plate under extreme working conditions, that is, the temperature is above 1300°C, so that the corresponding braking device can be used in, for example, CR 450 EMUs with higher running speeds. In the case of emergency braking, the EMU brake temperature can reach 1200°C, while the use of metal-based powder metallurgy materials with a high temperature limit temperature of 800°C or resin-based friction materials with a high temperature limit temperature of 400°C will inevitably cause melting and adhesion, resulting in the EMU being unable to operate; 5. The non-dense carbon ceramic friction material prepared by the present invention can be widely used in the fields of automobiles, airplanes, high-speed railways, large braking equipment, etc. due to its specific properties and structure, more specifically in the fields of wheel brake discs of fixed-wing UAVs, maglev train skids, helicopter rotor brakes, wind turbine yaw brakes, large crane brakes at docks, and military special vehicle brakes. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a SEM image of the non-dense carbon ceramic friction material of the present invention; Figure 2 This is a thermal decay braking curve diagram of the non-dense carbon ceramic friction material in Example 1 of the present invention; Figure 3 This is a thermal decay braking curve diagram of the metal-based powder metallurgy material in Comparative Example 1; Figure 4 This is a thermal decay braking curve diagram of the resin-based friction material in Comparative Example 2; Figure 5 This is a thermal decay braking curve diagram of the high-density carbon ceramic material in Comparative Example 3; Figure 6 This is a thermal decay braking curve diagram of the carbon-ceramic friction material prepared by using petroleum coke instead of the graphite powder in Example 1 in Comparative Example 4. DETAILED DESCRIPTION
[0044] The density and porosity in the following embodiments are tested by the drainage method, and the test standard is GB / T24529-2009; the test standard for the compressive strength is ISO 14544-2013. During the test, in order to ensure the reliability of the experimental results, the brake discs involved in the test in the embodiments of the present invention and the comparative examples are ordinary dense carbon ceramic brake discs of the same existing material.
[0045] Example 1 This embodiment provides a non-dense carbon ceramic friction material, and the preparation method thereof comprises the following steps: Step 1, weighing 25% of chopped carbon fibers in a length range of 3-6 mm, 5% of graphite powder, 40% of FeSi75, 5% of silicon carbide powder, 5% of boron nitride powder, and 20% of phenolic resin powder according to weight parts, and mixing the above-prepared raw materials at room temperature using a double-motion mixer for 30 minutes to obtain a mixed powder; Wherein, the carbon content of the chopped carbon fiber is ≥95wt.%; The graphite powder has a particle size of 150 meshes and a carbon content of ≥96wt.%; The particle size of the FeSi75 is 300 mesh; The particle size of the silicon carbide powder is 200 mesh; The particle size of the boron nitride powder is 800 mesh; The phenolic resin powder is thermosetting phenolic resin powder with a particle size of 400 meshes.
[0046] Step 2, heating, pressing and curing the mixed powder in step 1 to obtain a green blank; Specifically, the mixed powder is filled into a metal mold with a cylindrical structure, the metal mold is placed between the upper and lower pressing plates of a flat vulcanizer, the upper and lower pressing plates of the flat vulcanizer are heated to 80°C, and the temperature is kept for 10 minutes to liquefy the phenolic resin powder, and the remaining powder is bonded; after the temperature is kept, the upper and lower pressing plates of the flat vulcanizer are heated to 180°C, and a pressure of 20MPa is set to press the mold, and the pressure is released after the temperature is kept for 20 minutes, and the upper and lower pressing plates stop heating at the same time, and the mold is waited to cool naturally to room temperature, and the phenolic resin is solidified, so that the sample is then demolded and taken out to obtain a blank; Step 3, carbonizing the green body obtained in step 2 to obtain a C / C-Si body; Specifically, after evacuating to a vacuum degree of 10Pa, nitrogen is introduced into the furnace, the temperature is raised to 900°C at a rate of 2°C / min, and the temperature is kept for 2h. During the heating and heat preservation process, nitrogen is continuously introduced to maintain the pressure in the furnace at 0-0.04MPa; after the heat preservation is completed, heating is stopped, and nitrogen is stopped after the temperature in the furnace is lowered to 300°C, and the temperature in the furnace is continued to cool to room temperature, and the sample is taken out to obtain a C / C-Si blank; Step 4: siliconizing the C / C-Si blank obtained in step 3 with silicon powder to obtain the non-dense carbon ceramic friction material; the particle size of the silicon powder is 100 mesh, and the silicon purity is ≥99wt.%; Specifically, prepare silicon powder twice the weight of the C / C-Si blank in step 3, spread the silicon powder on the bottom of the graphite crucible, and place the C / C-Si blank obtained in step 3 on the silicon powder; place the graphite crucible in a high-temperature furnace, evacuate the furnace, raise the temperature in the furnace to 1600°C at a rate of 5°C / min, and keep it warm for 1 hour; stop heating after the insulation, wait for the temperature in the furnace to drop to room temperature, then take out the blank material after siliconization treatment to obtain a non-dense carbon ceramic friction material.
[0047] The total process time for preparing the non-dense carbon ceramic friction material in this embodiment is 7 days.
[0048] The average density of the non-dense carbon ceramic friction material prepared in this embodiment is 2.0 g / cm 3 ; Porosity is 20vol.%; High temperature resistance limit temperature is 1350℃; Compression strength is 80.5 MPa; Among them, the volume content of silicon carbide in the overall non-dense carbon-ceramic friction material is 24%.
[0049] In this embodiment, the SEM image of the non-dense carbon ceramic friction material is as follows: Figure 1 As shown, pores are dispersed in the material, and the pore sizes range from 10 to 200 μm. The light gray area is a granular Fe-Si alloy phase. The SiC introduced during the siliconizing process constitutes the skeleton of the material. Carbon fiber, graphite and boron nitride are dispersed in the material.
[0050] The metal mold shape in the preparation method of this embodiment is replaced with a mold in the shape of a friction plate, and a friction plate using the non-dense carbon ceramic friction material of this embodiment is prepared. The braking test is carried out using the AK-master test program to obtain the thermal decay braking curve. The specific method is: the temperature is gradually raised to 550°C for high-temperature thermal decay test, and a total of 15 uninterrupted braking tests are carried out, at 100km / h, with a deceleration of 40%, until the speed is reduced to 5km / h and stopped. The corresponding thermal decay braking curve of the test is as follows: Figure 2As shown, the blue curve (μ) is the instantaneous change curve of the friction coefficient of the brake disc and the friction pad from the beginning to the end of braking during each braking process; the pink point (μ) is the average friction coefficient record of one braking; the red curve (T) is the corresponding brake temperature, that is, after one braking ends, the next braking starts immediately, and the temperature rises; the gray curve (P) corresponds to the brake pressure. It can be seen that the friction performance (average friction coefficient, brake pressure) of the non-dense carbon-ceramic friction material prepared in this embodiment does not change substantially after the braking temperature increases. That is, the above-mentioned performance of the non-dense carbon-ceramic friction material prepared by the present invention is basically stable in 15 consecutive uninterrupted braking tests and will not be affected by factors such as temperature. In the AK-master program test, the wear amount of the friction plate is 77.1μm; the friction coefficient is stable between 0.6-0.7, and no thermal decay of the friction coefficient occurs; at the same time, the wear amount of the carbon-ceramic brake disc used in the test is 9μm.
[0051] Example 2 This embodiment provides a non-dense carbon ceramic friction material, and the preparation method thereof comprises the following steps: Step 1, weighing 20% of chopped carbon fibers in a length range of 3-6 mm, 10% of graphite powder, 30% of FeSi40, 10% of silicon carbide powder, 8% of boron nitride powder, and 22% of phenolic resin powder according to weight parts, and mixing the above-prepared raw materials at room temperature using a double-motion mixer for 40 minutes to obtain a mixed powder; Wherein, the carbon content of the chopped carbon fiber is ≥95wt.%; The graphite powder has a particle size of 150 meshes and a carbon content of ≥96wt.%; The particle size of the FeSi40 is 300 mesh; The particle size of the silicon carbide powder is 300 mesh; The particle size of the boron nitride powder is 800 mesh; The phenolic resin powder is thermosetting phenolic resin powder with a particle size of 600 meshes.
[0052] Step 2, heating, pressing and curing the mixed powder in step 1 to obtain a green blank; Specifically, the mixed powder is filled into a metal mold with a cylindrical structure, the metal mold is placed between the upper and lower pressing plates of a flat vulcanizer, the upper and lower pressing plates of the flat vulcanizer are heated to 80°C, and the temperature is kept for 5 minutes to liquefy the phenolic resin powder, and the remaining powder is bonded; after the temperature is kept, the upper and lower pressing plates of the flat vulcanizer are heated to 180°C, and a pressure of 20MPa is set to press the mold, and the pressure is released after the temperature is kept for 20 minutes, and the upper and lower pressing plates stop heating at the same time, and the mold is waited to cool naturally to room temperature, and the phenolic resin is solidified, so that the sample is demolded and taken out to obtain a blank; Step 3, carbonizing the green body obtained in step 2 to obtain a C / C-Si body; Specifically, after evacuating to a vacuum degree of 10Pa, nitrogen is introduced into the furnace, the temperature is raised to 900°C at a rate of 1°C / min, and the temperature is kept for 0.5h. During the heating and heat preservation process, nitrogen is continuously introduced to maintain the pressure in the furnace at 0-0.04MPa; after the heat preservation is completed, heating is stopped, and nitrogen is stopped after the temperature in the furnace drops to 300°C, and the temperature in the furnace is continued to cool to room temperature, and the sample is taken out to obtain a C / C-Si blank; Step 4: siliconizing the C / C-Si blank obtained in step 3 with silicon powder to obtain the non-dense carbon ceramic friction material; the particle size of the silicon powder is 100 mesh, and the silicon purity is ≥99wt.%; Specifically, prepare silicon powder twice the weight of the C / C-Si blank in step 3, spread the silicon powder on the bottom of the graphite crucible, and place the C / C-Si blank obtained in step 3 on the silicon powder; place the graphite crucible in a high-temperature furnace, evacuate the furnace, increase the temperature in the furnace to 1550°C at a rate of 5°C / min, and keep it warm for 2 hours; stop heating after the insulation is completed, wait for the temperature in the furnace to drop to room temperature, and then take out the blank material after siliconization treatment to obtain a non-dense carbon ceramic friction material.
[0053] The total process time for preparing the non-dense carbon ceramic friction material in this embodiment is 7 days.
[0054] The average density of the non-dense carbon ceramic friction material prepared in this embodiment is 2.1 g / cm 3 ; Porosity is 15vol.%; High temperature limit temperature is 1350℃; Compression strength is 82.9MPa; Among them, the volume content of silicon carbide in the overall non-dense carbon-ceramic friction material is 17%.
[0055] The shape of the metal mold in the preparation method of this embodiment is replaced with a mold in the shape of a friction plate, and a friction plate made of the non-dense carbon-ceramic friction material of this embodiment is prepared. In the AK-master program test, the wear amount of the friction plate is 63.9μm; the friction coefficient is stable between 0.6-0.7; and the wear amount of the carbon-ceramic brake disc used in the test is 13μm.
[0056] Example 3 This embodiment provides a non-dense carbon ceramic friction material, and the preparation method thereof comprises the following steps: Step 1, weighing 25% of chopped carbon fibers in a length range of 3-6 mm, 5% of graphite powder, 30% of FeSi65, 7% of silicon carbide powder, 3% of boron nitride powder, and 30% of phenolic resin powder according to weight, and mixing the above-prepared raw materials at room temperature using a double-motion mixer for 50 minutes to obtain a mixed powder; Wherein, the carbon content of the chopped carbon fiber is ≥95wt.%; The graphite powder has a particle size of 150 meshes and a carbon content of ≥96wt.%; The particle size of the FeSi65 is 150 mesh; The particle size of the silicon carbide powder is 200 mesh; The particle size of the boron nitride powder is 800 mesh; The phenolic resin powder is thermosetting phenolic resin powder with a particle size of 400 meshes.
[0057] Step 2, heating, pressing and curing the mixed powder in step 1 to obtain a green blank; Specifically, the mixed powder is filled into a metal mold with a cylindrical structure, the metal mold is placed between the upper and lower pressing plates of a flat vulcanizer, the upper and lower pressing plates of the flat vulcanizer are heated to 80°C, and the temperature is kept for 20 minutes to liquefy the phenolic resin powder, and the remaining powder is bonded; after the temperature is kept, the upper and lower pressing plates of the flat vulcanizer are heated to 180°C, and a pressure of 20MPa is set to press the mold, and the pressure is released after the temperature is kept for 30 minutes, and the upper and lower pressing plates stop heating at the same time, and the mold is waited to cool naturally to room temperature, and the phenolic resin is solidified, so that the sample is then demolded and taken out to obtain a blank; Step 3, carbonizing the green body obtained in step 2 to obtain a C / C-Si body; Specifically, after evacuating to a vacuum degree of 10Pa, nitrogen is introduced into the furnace, the temperature is raised to 900°C at a rate of 5°C / min, and the temperature is kept for 1h. During the heating and heat preservation process, nitrogen is continuously introduced to maintain the pressure in the furnace at 0-0.04MPa; after the heat preservation is completed, heating is stopped, and nitrogen is stopped after the temperature in the furnace is lowered to 300°C, and the temperature in the furnace is continued to cool to room temperature, and the sample is taken out to obtain a C / C-Si blank; Step 4: siliconizing the C / C-Si blank obtained in step 3 with silicon powder to obtain the non-dense carbon ceramic friction material; the particle size of the silicon powder is 150 mesh, and the silicon purity is ≥99wt.%; Specifically, prepare silicon powder twice the weight of the C / C-Si blank in step 3, spread the silicon powder on the bottom of the graphite crucible, and place the C / C-Si blank obtained in step 3 on the silicon powder; place the graphite crucible in a high-temperature furnace, evacuate the furnace, increase the temperature in the furnace to 1610°C at a rate of 5°C / min, and keep it warm for 1 hour; stop heating after the insulation, wait for the temperature in the furnace to drop to room temperature, then take out the blank material after siliconization treatment to obtain a non-dense carbon ceramic friction material.
[0058] The total process time for preparing the non-dense carbon ceramic friction material in this embodiment is 7 days.
[0059] The average density of the non-dense carbon ceramic friction material prepared in this embodiment is 1.8 g / cm 3 ; Porosity is 23vol.%; High temperature resistance limit temperature is 1350℃; Compression strength is 79.6MPa; Among them, the volume content of silicon carbide in the overall non-dense carbon-ceramic friction material is 21%.
[0060] The shape of the metal mold in the preparation method of this embodiment is replaced with a mold in the shape of a friction plate, and a friction plate made of the non-dense carbon-ceramic friction material of this embodiment is prepared. In the AK-master program test, the wear amount of the friction plate is 95.0 μm; the friction coefficient is stable between 0.6-0.7; and the wear amount of the carbon-ceramic brake disc used in the test is 8 μm.
[0061] Example 4 This embodiment provides a non-dense carbon ceramic friction material, and the preparation method thereof comprises the following steps: Step 1, according to weight parts, weigh 15% of chopped carbon fibers in the length range of 3-6 mm, 5% of graphite powder, 50% of FeSi90, 5% of silicon carbide powder, 5% of boron nitride powder, and 20% of phenolic resin powder, and use a double-motion mixer to mix the above-prepared raw materials at room temperature for 60 minutes to obtain a mixed powder; Wherein, the carbon content of the chopped carbon fiber is ≥95wt.%; The graphite powder has a particle size of 150 meshes and a carbon content of ≥96wt.%; The particle size of the FeSi90 is 200 mesh; The particle size of the silicon carbide powder is 300 mesh; The particle size of the boron nitride powder is 1000 mesh; The phenolic resin powder is thermosetting phenolic resin powder with a particle size of 600 meshes.
[0062] Step 2, heating, pressing and curing the mixed powder in step 1 to obtain a green blank; Specifically, the mixed powder is filled into a metal mold with a cylindrical structure, the metal mold is placed between the upper and lower pressing plates of a flat vulcanizer, the upper and lower pressing plates of the flat vulcanizer are heated to 80°C, and the temperature is kept for 30 minutes to liquefy the phenolic resin powder, and the remaining powder is bonded; after the temperature is kept, the upper and lower pressing plates of the flat vulcanizer are heated to 180°C, and a pressure of 20MPa is set to press the mold, and the pressure is released after the temperature is kept for 20 minutes, and the upper and lower pressing plates stop heating at the same time, and the mold is waited to cool naturally to room temperature, and the phenolic resin is solidified, so that the sample is then demolded and taken out to obtain a blank; Step 3, carbonizing the green body obtained in step 2 to obtain a C / C-Si body; Specifically, after evacuating to a vacuum degree of 10Pa, nitrogen is introduced into the furnace, the temperature is raised to 900°C at a rate of 4°C / min, and the temperature is kept for 2.5 hours. During the heating and heat preservation process, nitrogen is continuously introduced to maintain the pressure in the furnace at 0-0.04MPa; after the heat preservation is completed, heating is stopped, and nitrogen is stopped after the temperature in the furnace is lowered to 300°C, and the temperature in the furnace is continued to cool to room temperature, and the sample is taken out to obtain a C / C-Si blank; Step 4: siliconizing the C / C-Si blank obtained in step 3 with silicon powder to obtain the non-dense carbon ceramic friction material; the particle size of the silicon powder is 100 mesh, and the silicon purity is ≥99wt.%; Specifically, prepare silicon powder twice the weight of the C / C-Si blank in step 3, spread the silicon powder on the bottom of the graphite crucible, and place the C / C-Si blank obtained in step 3 on the silicon powder; place the graphite crucible in a high-temperature furnace, evacuate the furnace, raise the temperature in the furnace to 1650°C at a rate of 5°C / min, and keep it warm for 1.5 hours; stop heating after the insulation is completed, wait for the temperature in the furnace to drop to room temperature, then take out the blank material after siliconization treatment to obtain a non-dense carbon ceramic friction material.
[0063] The total process time for preparing the non-dense carbon ceramic friction material in this embodiment is 7 days.
[0064] The average density of the non-dense carbon ceramic friction material prepared in this embodiment is 2.2 g / cm 3 ; Porosity is 15vol.%; High temperature limit temperature is 1350℃; Compression strength is 78.1 MPa; Among them, the volume content of silicon carbide in the overall non-dense carbon-ceramic friction material is 28%.
[0065] The shape of the metal mold in the preparation method of this embodiment is replaced with a mold in the shape of a friction plate, and a friction plate made of the non-dense carbon-ceramic friction material of this embodiment is prepared. In the AK-master program test, the wear amount of the friction plate is 80.3μm; the friction coefficient is stable between 0.6-0.7; and the wear amount of the carbon-ceramic brake disc used in the test is 11μm.
[0066] Example 5 This embodiment provides a non-dense carbon ceramic friction material, and the preparation method thereof comprises the following steps: Step 1, according to weight parts, weigh 35% of chopped carbon fibers in the length range of 3-6 mm, 5% of graphite powder, 10% of FeSi75, 20% of FeSi90, 10% of silicon carbide powder, 5% of boron nitride powder, and 15% of phenolic resin powder, and use a double-motion mixer to mix the above-prepared raw materials at room temperature for 20 minutes to obtain a mixed powder; Wherein, the carbon content of the chopped carbon fiber is ≥95wt.%; The graphite powder has a particle size of 150 meshes and a carbon content of ≥96wt.%; The particle size of the FeSi75 is 300 mesh; The particle size of the FeSi90 is 300 mesh; The particle size of the silicon carbide powder is 200 mesh; The particle size of the boron nitride powder is 800 mesh; The phenolic resin powder is thermosetting phenolic resin powder with a particle size of 500 meshes.
[0067] Step 2, heating, pressing and curing the mixed powder in step 1 to obtain a green blank; Specifically, the mixed powder is filled into a metal mold with a cylindrical structure, the metal mold is placed between the upper and lower pressing plates of a flat vulcanizer, the upper and lower pressing plates of the flat vulcanizer are heated to 80°C, and the temperature is kept for 25 minutes to liquefy the phenolic resin powder, and the remaining powder is bonded; after the temperature is kept, the upper and lower pressing plates of the flat vulcanizer are heated to 180°C, and a pressure of 20MPa is set to press the mold, and the pressure is released after the temperature is kept for 30 minutes, and the upper and lower pressing plates stop heating at the same time, and the mold is waited to cool naturally to room temperature, and the phenolic resin is solidified, so that the sample is demolded and taken out to obtain a blank; Step 3, carbonizing the green body obtained in step 2 to obtain a C / C-Si body; Specifically, after evacuating to a vacuum degree of 10Pa, nitrogen is introduced into the furnace, the temperature is raised to 900°C at a rate of 2°C / min, and the temperature is kept for 3 hours. During the heating and heat preservation process, nitrogen is continuously introduced to maintain the pressure in the furnace at 0-0.04MPa; after the heat preservation is completed, heating is stopped, and nitrogen is stopped after the temperature in the furnace is lowered to 300°C, and the temperature in the furnace is continued to cool to room temperature, and the sample is taken out to obtain a C / C-Si blank; Step 4: siliconizing the C / C-Si blank obtained in step 3 with silicon powder to obtain the non-dense carbon ceramic friction material; the particle size of the silicon powder is 150 mesh, and the silicon purity is ≥99wt.%; Specifically, prepare silicon powder twice the weight of the C / C-Si blank in step 3, spread the silicon powder on the bottom of the graphite crucible, and place the C / C-Si blank obtained in step 3 on the silicon powder; place the graphite crucible in a high-temperature furnace, evacuate the furnace, increase the temperature in the furnace to 1590°C at a rate of 5°C / min, and keep it warm for 2 hours; stop heating after the insulation is completed, wait for the temperature in the furnace to drop to room temperature, and then take out the blank material after siliconization treatment to obtain a non-dense carbon ceramic friction material.
[0068] The total process time for preparing the non-dense carbon ceramic friction material in this embodiment is 7 days.
[0069] The average density of the non-dense carbon ceramic friction material prepared in this embodiment is 1.9 g / cm 3 ; Porosity is 25vol.%; High temperature resistance limit temperature is 1350℃; Compression strength is 80.5 MPa; Among them, the volume content of silicon carbide in the overall non-dense carbon-ceramic friction material is 25%.
[0070] The shape of the metal mold in the preparation method of this embodiment is replaced with a mold in the shape of a friction plate, and a friction plate made of the non-dense carbon-ceramic friction material of this embodiment is prepared. In the AK-master program test, the wear amount of the friction plate is 89.4μm; the friction coefficient is stable between 0.6-0.7; and the wear amount of the carbon-ceramic brake disc used in the test is 8μm.
[0071] Comparative Example 1 This comparative example is a metal-based powder metallurgy material prepared according to the literature: Zhao SQ, Yan QZ, Peng T, et al. The braking behaviors of Cu-based powder metallurgy brake pads mated with C / C-SiC diskfor high-speed train. Wear, 2020, 448-449:203237.
[0072] The average density of the metal-based powder metallurgy material prepared in this comparative example is 6.1 g / cm 3 , which is about 3 times the density of the non-dense carbon ceramic friction material of the present invention; the porosity is 15.7 vol.%; the high temperature limit temperature is 800℃; the compressive strength is 104.3MPa; In this comparative example, the friction plate prepared from the metal-based powder metallurgy material was subjected to a braking test using the AK-master test program. The test method was the same as in Example 1, and a thermal decay braking curve was obtained as shown in FIG. Figure 3 As shown. It can be seen that with the increase of brake temperature and the increase of friction times, the instantaneous change curve of the friction coefficient of the friction plate prepared by the metal-based powder metallurgy material of this comparative example fluctuates relatively greatly, and the average friction coefficient shows a decreasing trend. It can also be seen that the braking pressure gradually increases. That is to say, the above-mentioned performance of the friction plate prepared by the metal-based powder metallurgy material of this comparative example is not as stable as the performance of the friction plate prepared by the non-dense carbon ceramic friction material of the present invention in 15 consecutive uninterrupted braking tests. The friction plate prepared by the metal-based powder metallurgy material of this comparative example has a wear amount of 185.7μm in the AK-master program test; the friction coefficient is 0.5-0.7; and the wear amount of the carbon ceramic brake disc used in the test is 120.5μm.
[0073] The reason why the performance of the above-mentioned metal-based powder metallurgy friction material is not stable is that in the braking process, the friction plate prepared by the comparative example generates a transient hot spot (temperature exceeding 1000°C) locally, and the Cu matrix of the local position of the powder metallurgy friction plate softens or melts, and adheres to the surface of the carbon-ceramic brake disc grinding against it, resulting in uneven viscous resistance, which leads to unstable friction performance. At the same time, the main reason for the large wear is that the powder metallurgy friction material is mainly composed of a metal matrix, and its hardness is much lower than the ceramic phase hardness of the carbon-ceramic brake disc grinding against it. It is more easily cut by the hard ceramic phase of the brake disc friction surface during the braking process, thereby causing wear.
[0074] Comparative Example 2 This comparative example provides a resin-based friction material and a preparation method thereof in the prior art, and the specific steps are as follows: 30 parts by mass of boron-modified phenolic resin powder, 5 parts by mass of steel fiber, 10 parts by mass of carbon fiber, 1 part by mass of aluminum titanate, 1 part by mass of Al2O3, 8 parts by mass of SiO2, 2 parts by mass of MgO, 1 part by mass of BaSO4, 10 parts by mass of graphite, 3 parts by mass of MoS2, 5 parts by mass of SiC, 0.8 parts by mass of antimony oxide and 1 part by mass of barite are mixed evenly, the mixed powder is put into a mold, the mold is heated to 180°C, a pressure of 40MPa is applied using a flat vulcanizer, the mold is demolded after keeping the heat and pressure for 20 minutes, and then the material is placed in an electric heated blast drying oven for heat treatment at a temperature of 200°C for 12 hours to obtain the resin-based friction material in this comparative example.
[0075] The average density of the resin-based friction material prepared in this comparative example is 3.3 g / cm 3 ; Porosity is 6.7vol.%; High temperature resistance limit temperature is 400℃; Compression strength is 79.6 MPa; In this comparative example, the friction plate prepared from the resin-based friction material was subjected to a braking test using the AK-master test procedure. The test method was the same as in Example 1, and a thermal decay braking curve was obtained as shown in FIG. Figure 4As shown. It can be seen that with the increase of brake temperature and the increase of friction times, the instantaneous change curve of the friction coefficient of the friction plate prepared by the resin-based material of this comparative example shows an obvious downward trend, and the average friction coefficient shows a decreasing trend. It can also be seen that the brake pressure gradually increases and is unstable, with obvious thermal decay problems. That is, the above-mentioned performance of the friction plate prepared by the resin-based friction material of this comparative example is not as stable as the performance of the friction plate prepared by the non-dense carbon-ceramic friction material of the present invention in 15 consecutive uninterrupted braking tests. The friction plate prepared by the resin-based friction material of this comparative example has a wear amount of 534.4μm in the AK-master program test; the friction coefficient is 0.3-0.5; and the wear amount of the carbon-ceramic brake disc used in the test is 470.1μm.
[0076] The reason why the performance of the above-mentioned resin-based friction materials is not stable enough is that the resin-based friction materials rely on resin to bond more than a dozen other fillers together. The resin decomposes above 400°C and cannot effectively bond to other fillers. Therefore, the friction coefficient is prone to fluctuate with changes in the friction surface components. Without the bonding of the resin, other components are more likely to be ground off, resulting in a large amount of wear.
[0077] Comparative Example 3 This comparative example is based on the literature: Shangwu Fan, Litong Zhang, Yongdong Xu, et al. Microstructure and properties of 3D needle-punched carbon / silicon carbidebrake materials. Composites Science and Technology. 2007, 67: 2390-2398. The high-density carbon ceramic material prepared by chemical vapor deposition has a total process cycle of three months, which is much longer than the process cycle of preparing the non-dense carbon ceramic friction material of the present invention, and the time cost is high.
[0078] The average density of the high-density carbon ceramic material prepared in this comparative example is 2.1 g / cm 3 ; Porosity is 6.3vol.%; High temperature limit temperature is 1350℃; Compression strength is 212 MPa; In this comparative example, the friction plate made of the high-density and low-porosity carbon ceramic material was subjected to a braking test using the AK-master test procedure. The test method was the same as in Example 1, and the thermal decay braking curve was obtained as shown in FIG. Figure 5As shown. It can be seen that with the increase of brake temperature and the increase of friction times, the instantaneous change curve of the friction coefficient of the friction plate prepared by the dense low-porosity carbon ceramic material in this comparative example has a large fluctuation range and is unstable, and the average friction coefficient shows a trend of vibration reduction. It can also be seen that the brake pressure gradually increases and is unstable. That is, the above-mentioned performance of the friction plate prepared by the high-density and low-porosity carbon ceramic material in this comparative example is not as stable as the performance of the friction plate prepared by the non-dense carbon ceramic friction material of the present invention in 15 consecutive uninterrupted braking tests. The friction plate prepared by the high-density carbon ceramic material of this comparative example has a wear amount of 412μm in the AK-master program test; the friction coefficient is 0.6-0.9, and the wear amount of the carbon ceramic brake disc used in the test is 98μm.
[0079] The reason why the performance of the above-mentioned carbon-ceramic friction material is not stable enough is that the carbon-ceramic brake disc and friction plate of the same material are rubbed against each other. Since the material composition is C, Si and SiC, these three phases are all brittle phases. When the discs are rubbed against each other, they will produce brittle peeling. The peeled Si and SiC have high hardness and remain between the friction surfaces to play the role of hard abrasives, resulting in a "three-body" abrasive wear effect. The mechanical engagement and shearing of the hard micro-protrusions and abrasives lead to unstable friction performance. The severe abrasive wear effect leads to high wear.
[0080] Comparative Example 4 This comparative example provides a carbon ceramic friction material, using petroleum coke instead of the graphite powder in Example 1, and its preparation method is the same as that in Example 1: The average density of the carbon ceramic friction material prepared in this comparative example is 2.0 g / cm 3 ; Porosity is 25.6vol.%; High temperature resistance limit temperature is 900℃; Compression strength is 62.5MPa.
[0081] In this comparative example, the friction plate prepared from the carbon ceramic friction material was subjected to a braking test using the AK-master test procedure. The test method was the same as in Example 1, and a thermal decay braking curve was obtained as shown in FIG. Figure 6 As shown. It can be seen that with the increase of brake temperature and the increase of friction times, the instantaneous change curve of the friction coefficient of this comparative example has a large fluctuation range and is unstable, and the average friction coefficient shows a trend of first rising and then falling. It can also be seen that the brake pressure is also unstable. In other words, the above-mentioned performance of the friction plate prepared by the carbon-ceramic friction material of this comparative example is not as stable as the performance of the friction plate prepared by the non-dense carbon-ceramic friction material of the present invention in 15 consecutive uninterrupted braking tests. The friction plate prepared by the carbon-ceramic friction material of this comparative example has a wear amount of 228.9μm in the AK-master program test; the friction coefficient is 0.6-0.8; and the wear amount of the carbon-ceramic brake disc used in the test is 159.7μm.
[0082] The reason why the performance of the above-mentioned carbon ceramic friction material is not stable enough is mostly because the composition of petroleum coke is complex and mostly in granular form, which affects the friction performance. The graphite powder selected in the present invention has a lamellar structure and has very excellent lubricating properties. Adding graphite powder is beneficial to the lubrication effect during braking, slowing down the abrasive wear caused by hard particles on the mill, thereby stabilizing the friction coefficient and reducing the amount of material wear.
[0083] It should be understood that the present invention is not limited to what has been described above and shown in the accompanying drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A non-dense carbon ceramic friction material, characterized in that: The non-dense carbon ceramic friction material is obtained by subjecting a C / C-Si blank to siliconization treatment with silicon powder, wherein the raw materials for preparing the C / C-Si blank include chopped carbon fiber, graphite powder, ferrosilicon mixture, silicon carbide powder, boron nitride powder, and phenolic resin powder; The non-dense carbon ceramic friction material has a porosity of 15-25 vol.%, a high temperature resistance limit temperature of 1350° C., and a compressive strength of 80.5±2.4 MPa.
2. The non-dense carbon ceramic friction material according to claim 1, characterized in that: In parts by weight, the components and proportions in the raw materials for preparing the C / C-Si blank are as follows: Chopped carbon fiber: 15-35%; Graphite powder: 5-10%; Ferrosilicon mixture: 30-50%; Silicon carbide powder: 5-10%; Boron nitride powder: 3-8%; Phenolic resin powder: 15-30%.
3. The non-dense carbon ceramic friction material according to claim 1, characterized in that: The mass ratio of the C / C-Si blank to the silicon powder is 1:
2.
4. A method for preparing the non-dense carbon ceramic friction material according to any one of claims 1 to 3, characterized in that: The steps include: Step 1, weighing short carbon fiber, graphite powder, ferrosilicon alloy powder, silicon carbide powder, boron nitride powder, and phenolic resin powder, and mixing them to obtain a mixed powder; Step 2, heating, pressing and curing the mixed powder in step 1 to obtain a green blank; Step 3, carbonizing the green body obtained in step 2 to obtain a C / C-Si body; Step 4: using silicon powder to perform melt siliconization treatment on the C / C-Si blank obtained in step 3 to obtain the non-dense carbon ceramic friction material.
5. A friction plate, characterized in that: The friction plate is made of the non-dense carbon-ceramic friction material according to any one of claims 1 to 3; In the AK-master program test, the wear amount of the friction plate is 52.8-95.0 μm; The friction coefficient is 0.6-0.
7.
6. A braking device, characterized in that: The braking device comprises the friction plate according to claim 5.
7. The braking device according to claim 6, characterized in that: The braking device further comprises a brake disc.
8. A car, characterized in that: The automobile comprises the braking device according to any one of claims 6-7.
9. An aircraft, characterized in that: The aircraft comprises the braking device according to any one of claims 6-7.
10. A high-speed railway, characterized in that: The high-speed railway comprises the braking device described in any one of claims 6-7.
Citation Information
Patent Citations
Low-cost carbon-ceramic brake material and preparation method thereof
CN117024152A
Cited By
Non-dense carbon-ceramic friction material, and preparation method therefor and use thereof
WO2026129603A1